miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.